The relationship of reactive and planned agility and selected motor indicators to game performance of female players in volleyball - Paška, L.; Horicka, P.; Šimonek, J. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The main goal of our research was to determine the relationship of different types of agility and selected motor indicators to the game performance of female volleyball players. There were 10 players (average age 17.2 ± 2,27 y.; height 173.2 ± 9,8 cm), in the team of Volley Project UKF Nitra. Witty SEM system and photocells (Microgate) and Fitro Jumper (Fitronic) were used for testing. Then there were used T agility test, velocity (5m and 10m sprint) and explosive strength of the lower limbs (DJ, CMJ, Swing). Evaluation of game performance was realized by the sports analysis tool Data Volley 4 (Data Project). We found relationship between the indicator of game performance "Vote" with velocity 5m sprint (r = -0.587, p = 0.074) and the indicator of explosive strength of the lower limbs DJ (r = 0.552, p = 0.098). Another relationship at the 5% (p<0.05) level of statistical significance with opposite polarity between the "Defensive Agility" test and the game performance indicator "Vote" (r = -0.685, p = 0.029). Other statistically significant relationships are between indicators of the explosive strength of the lower limbs (DJ, CMJ, Swing) and the 10m sprint, and between DJ and CMJ with tests of reactive agility "Defensive Agility" and planned agility (T agility test). Based on the results of our research, we recommend trainers to focus on the development of agility and the improvement of speed and strength abilities in the training process.